A study of the mechanical behavior of rectangular steel tubular column strengthened using intermittent welding angle steel. (October 2021) - Jian, Xiangyang; Liu, Haiqing; Zhao, Zhongwei; Wu, Xiufeng; Lei, Ming; Chen, Zimu
Abstract: From the perspective of the development of steel structures in China, the existing steel structure had experienced decades of service. However, due to the change of its functionality, and the erosion caused due to the surrounding environment, reinforcement of steel has become necessary. Thus, the research on reinforcement theory and methods of the existing steel structures has become an important measure in the "reinforcement period". Steel angle welding on the surface of steel columns is a common method used in practical engineering. However, the traditional continuous welding angle steel reinforcement of rectangular steel pipe columns leads to a large amount of welding work on the construction site, thus prolonging the construction time and increase the project cost. Moreover, the quality of welding also cannot be guaranteed. Therefore, in order to reduce the cost of field welding and reinforcement of the construction project, intermittent welding is proposed in this work. In this paper, the finite element analysis of rectangular steel tube column models that were strengthened using different intermittent welded angle steel under axial and eccentric compression is discussed out and the results are compared with the experimental results for validation. Further, a large number of numerical models with different parameters are analyzed. From the analysis, the ultimate bearing capacity and the load transfer mechanism of the rectangular steel tube columns that were strengthened using intermittent angle steel under eccentric and axial compression are studied, and the optimal weld spacing and weld length are obtained. The results provide a theoretical base for future practical engineering applications.